The impact of green human resource management on the performance results of small and medium-sized enterprises in Binh Duong province - Bui , Thị Hường (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
This study was conducted to determine the factors of green human resource management (GHRM) that impact the performance of small and medium enterprises in Binh Duong province. Primary data was collected from 304 businesses operating in Binh Duong province. The research used a combination of qualitative and quantitative research methods with the support of SPSS 25.0 software to analyze data. The results show that there are 6 factors of GHRM that have a positive influence on the performance of small and medium-sized enterprises in Binh Duong province and are arranged in descending order of impact as follows: Training and development green (β = 0.258), green performance management (β = 0.240), green recruitment (β = 0.205), green job design and analysis (β = 0.155), green incentives (β = 0.135 ), green labor relations (β = 0.133).